CEST imaging combined with 1H-MRS reveal the neuroprotective effects of riluzole by improving neurotransmitter imbalances in Alzheimer’s disease mice - Yuanyu Shen; Xiaolei Zhang; Siqi Liu; Lijing Xin; Wentao Xuan; Caiyu Zhuang; Yue Chen; Beibei Chen; Xinhui Zheng; Renhua Wu; Yan Lin (Alzheimer’s Research & Therapy, 2025)
Abstract Background The imbalance of glutamate (Glu) and gamma-aminobutyric acid (GABA) neurotransmitter system plays a crucial role in the pathogenesis of Alzheimer’s disease (AD). Riluzole is a Glu modulator originally approved for amyotrophic lateral sclerosis that has shown potential neuroprotective effects in various neurodegenerative disorders. However, whether riluzole can improve Glu and GABA homeostasis in AD brain and its related mechanism of action remain unknown. This study utilized chemical exchange saturation transfer (CEST) imaging combined with proton magnetic resonance spectroscopy (1H-MRS) to monitor the dynamic changes of Glu and GABA in riluzole-treated AD mice, aiming to evaluate the efficacy and mechanism of riluzole in AD treatment. Methods GluCEST, GABACEST and 1H-MRS were used to longitudinally monitor Glu and GABA levels in 3xTg AD mice treated with riluzole (12.5 mg/kg/day) or vehicle for 20 weeks. Magnetic resonance measurements were performed at baseline, 6, 12, and 20 weeks post-treatment. Cognitive performance was assessed using the Morris Water Maze (MWM) at baseline, 10, and 20 weeks. At the study endpoint, immunohistochemistry, Nissl staining, and Western blot were used to evaluate the brain pathology, neuronal survival, and protein expression. Results GluCEST, GABACEST and 1H-MRS consistently revealed higher levels of Glu and GABA in the brain of riluzole-treated AD mice compared to untreated controls, which were associated with improvements in spatial learning and memory. The cognitive improvements significantly correlated with the increased GluCEST signals and Glu levels. Immunohistochemistry and Nissl staining demonstrated that riluzole treatment reduced amyloid-beta (Aβ) deposition, tau hyperphosphorylation, GFAP-positive astrocyte activation, and prevented neuronal loss. Moreover, riluzole upregulated the expression of excitatory amino acid transporter 2 (EAAT2), glutamic acid decarboxylase 65/67 (GAD65/67), and glutamine synthetase (GS), suggesting enhanced neurotransmitter metabolism. Conclusions CEST imaging combined with 1H-MRS demonstrated the effectiveness of riluzole in modulating Glu- and GABA-related changes and improving cognitive function in 3xTg AD mice, potentially through regulating key proteins involved in neurotransmitter metabolism. These findings suggest riluzole as a therapeutic agent for Alzheimer’s disease and highlight the utility of multimodal MR imaging in monitoring treatment response and exploring disease mechanisms.